Research ability and research motivation of postgraduate nursing students in traditional Chinese medicine colleges - Jia‐Hui Zhang; Shu‐Qin Pang; Li Ge; Guan‐Ming Wang; Zong‐Ting Luo; Xue‐Pei Hong; Xin‐yu Li (Wiley, 2022)
Abstract Aim To investigate the relationship between research ability and research motivation of postgraduate nursing students in traditional Chinese medicine colleges and identify other factors that may have an impact on the research ability of postgraduate nursing students. Design A cross‐sectional electronic survey was used to collect data from 191 postgraduate nursing students. Methods A total of 191 postgraduate nursing students from seven traditional Chinese medicine colleges were investigated from October to November 2020 using self‐rated scales for research ability and research motivation. The relationship between the variables affecting the research ability of postgraduate nursing students in traditional Chinese medicine colleges was determined. Results There was a positive correlation between the score of self‐rated research ability and research motivation among 191 postgraduate nursing students in traditional Chinese medicine colleges. Multiple stepwise regression analysis showed that grade, research motivation, age and active participation in class discussions were the main factors affecting the self‐rated research ability. Conclusion The self‐rated research ability of postgraduate nursing students in traditional Chinese medicine colleges is positively correlated with research motivation. According to the research motivation orientation, adopting targeted training methods and establishing correct professional understanding may improve the research ability of postgraduate nursing students.